Pengembangan Model Pembelajaran Tematik Berdasarkan Brain Based Learning - Afib Rulyansah & Uswatun Hasanah (Tarbiyatuna Kajian Pendidikan Islam, 2018)
Based on what happened in the teachers have not been able to apply the model of learning in the classroom. The implementation of thematic learning in elementary school is a real step in improving students' abilities. This research was conducted in Class IV SDN Kebonsari 5 Kota Probolinggo with the aim to produce thematic learning model based on Brain Based Learning. The resulting product is a thematic learning model based on Brain Based Learning which has a level of validity and stability. Development method with Bord and Gall model. Referring from the research procedure, the results of this study showed that the validation test results of experts stated very valid with an average score of 87.8%. Level of product absorption with score 84%.